Inducing human capital formation: Migration as a substitute for subsidies - Oded Stark; Yong Wang (Institute for Advanced Studies (IHS), 2001)
When productivity is fostered by an individual's own human capital as well as by the economy-wide average level of human capital, individuals under-invest in human capital. The provision of subsidies for the formation of human capital, conditional on the subsidy being self-financed by tax revenues, can bring the economy to its socially optimal level of human capital. Yet a strictly positive probability of migration to a richer country, by raising both the level of human capital formed by optimizing individuals in the home country and the average level of human capital of non-migrants in the country, can enhance welfare and nudge the economy toward the social optimum. Indeed, under a well-controlled, restrictive migration policy the welfare of all workers is higher than in the absence of this policy.
Keywords: F22; H23; I30; J24; J61; 330; migration; human capital formation; externalities; social welfare; Humankapital; Internationale Arbeitsmobilität; Externer Effekt; Theorie